Talented people and strong brands: The contribution of human capital and brand equity to firm value - Vomberg, Arnd; Homburg, Christian; Bornemann, Torsten (Strategic Management Journal, 2015)
Research and managerial practice generally contend that human capital and brand equity constitute a company's most valuable resources. Relying on similar underlying theoretical rationales, research on the value relevance of these two resources has developed in different disciplines. Combining diverse data sources, the authors examine the simultaneous effects of brand equity and human capital on firm value. In addition, they consider how much the effects of these two resources differ between services and manufacturing. Results provide evidence for a complementary relationship between human capital and brand equity and show that both resources create relatively more value in a service setting . Copyright © 2014 John Wiley & Sons, Ltd.